Characteristics of AC-BC Asphalt Concrete Mix Using Oil Asphalt and LGA Asbuton as Binders - Lakawa, Irwan; Sulaiman; Desti Ayu Wulandari (International Journal of Management and Education in Human Development, 2022)
Indonesia has natural asphalt located in Southeast Sulawesi Province, especially at Buton Island, called asbuton which can be utilized as a binder on road pavements to replace oil asphalt through an extraction process to separate the bitumen and asbuton minerals. The aim of this study is to analyze the characteristics of asbuton asphalt that will be used in the AC-BC mixture and to analyze the characteristics of the asphalt mixture produced from a mixture of oil asphalt and asbuton LGA as a binder in the AC-BC asphalt mixture. The test results of the AC-BC asphalt mixture in the form of aggregate, 60-70 penetration bitumen, bitumen extracted from asbuton, and gradation of the combined mixture showed results that correspond to the requirements of Bina Marga. Characteristics of AC-BC asphalt mixture applied a test method with Marshall tool. The mixture test result by adding LGA levels asbuton of 0%, 2%, 3,5%, and 5% as a substitute for penetration bitumen 60-70, the values of Stability, melting (flow), Marshall Quotient (MQ), and Voids Filled Bitumen (VFB) experienced an increase, while the Void in Mix (VIM) and the Voids in Mineral Aggregate (VMA) decreased and met the specifications set by Bina Marga. However, the 5% LGA level did not meet the specifications for melting (flow) values